Analysis of Academic Ability Test (TKA) Policy at SMAN 1 and SMAN 2 Palangka Raya - Septi Ayana, Riya; Nordianingsih, Meltiani; Nurmala Sari, Tanti; Dakir, Dakir; Baehaqi, Luqman (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2025)
This study aims to analyze the implementation of the Academic Ability Test (TKA) as a new policy of the Ministry of Education in 2025 which is applied to grade XII students, focusing on its implementation in SMAN 1 Palangka Raya and SMAN 2 Palangka Raya. TKA is designed to measure students' critical, logical, and analytical thinking skills, as well as being an instrument for mapping the quality of education and the basis for decision-making for students, schools, and the government. This research uses the Systematic Literature Review (SLR) method based on the PRISMA 2020 protocol, and is strengthened with a literature review to provide a comprehensive understanding of the concepts, objectives, benefits, and challenges of TKA. Field findings show that the implementation of TKA in both schools runs in an orderly manner, but presents diverse experiences for students. Subjects such as Mathematics, Physics, and English (reading section) are the most difficult, while Indonesian and basic English are considered more relevant to the learning material. Processing time is the main obstacle, especially for questions that require in-depth analysis. In addition, some students feel that some questions do not fully fit the grid, and their preparation is hampered by the school's heavy academic load. Overall, TKA has an important role in mapping students' academic abilities, but improvements are needed in terms of exam duration, student readiness, and instrument suitability so that this policy can run more effectively and support the improvement of the quality of education at the high school level.